Deep rock mechanics : from research to engineering : proceedings of the international conference on the geo-mechanics, geo-energy, and geo-resources (IC3G 2018), Chengdu, P.R. China, 22-24 September 2018 /: from research to engineering : proceedings of the international conference on the geo-mechanics, geo-energy, and geo-resources (IC3G 2018), Chengdu, P.R. China, 22-24 September 2018. ([2019]) - Unknown
No abstract available